Prior Consultation as a Mandate for the Governance of Aquatic Genetic Resources and their Associated Traditional Knowledge - Vargas-Chaves, Iván (2026)
Bioprospecting in aquatic ecosystems offers enormous potential for innovation but carries serious risks of biopiracy, which are amplified by the fluid and interconnected nature of these environments. The objective of this reflection paper is to argue that bioprospecting, without effective regulation such as Free, Prior, and Informed Consent (FPIC), violates the sovereignty and well-being of local and indigenous communities. Through documentary analysis methodology, academic literature and international legal frameworks, such as ILO Convention 169, it is critically examined to support the thesis. The results reveal that challenges like the «diffuse property» and «interconnected impact» of aquatic resources render traditional consultation models insufficient, facilitating the appropriation of traditional knowledge and threatening food and cultural security. It is concluded that FPIC is not an option but an indispensable legal and ethical imperative. This mechanism, which includes the communities' right to refuse consent, is the tool to rebalance power, ensure fair benefit-sharing, and protect the biocultural heritage of the peoples who steward these vital ecosystems.